Reaching Absent and Refusing Individuals During Home-Based HIV Testing Through Self-Testing—at What Cost? - Amstutz, Alain; Matsela, Lineo; Lejone, Thabo Ishmael; Kopo, Mathebe; Glass, Tracy Renée; Labhardt, Niklaus Daniel (Frontiers in Medicine, 2021)
Introduction In the HOSENG trial (NCT03598686), secondary distribution of oral self-tests for persons absent or refusing to test during a home-based HIV testing campaign in rural Lesotho resulted in an increase in testing coverage of 21% compared to a testing campaign without secondary distribution. This study aims to determine the per patient costs of both HOSENG trial arms. Method We conducted a micro-costing study to estimate the cost of home-based HIV testing with and without secondary self-test distribution from a provider’s perspective. A mixture of top-down and bottom-up costing was used. We estimated both the financial and economic per patient costs of each possible testing scenario. Costs were adjusted to 2018 US$. Results The overall provider cost for delivering the home-based HIV testing with secondary distribution was US$36'481 among the 4174 persons enumerated and 3094 eligible for testing in the intervention villages, compared to US$28'620 for 3642 persons enumerated and 2727 eligible for testing in control. The cost per person eligible for testing was US$11.79 in intervention versus US$10.50 in control. This difference was mainly driven by the cost of distributed oral self-tests. The cost per person tested was, however, lower in intervention villages (US$15.70 vs US$22.15) due to the higher testing coverage achieved through self-test distribution. Cost per person confirmed new HIV+ was US$889.79 in intervention and US$753.17 in control. Conclusion During home-based HIV testing in Lesotho, secondary distribution of self-tests for persons absent or refusing to test during the visit reduced costs per person tested.